Embolamentos : sociabilidades juvenis delitivas em contexto de periferia - Acosta, Suélen Pinheiro Freire (Universidade do Vale do Rio dos Sinos, 2019)
The present research analyzes the process of reconfiguration of youth sociability practices observed in suburbs contexts. The focus is on practices where violence presents itself as a central element, receiving different meanings according to the context observed. The analysis turns to Guajuviras and Mathias Velho neighborhoods, located in the municipality of Canoas, because they are areas marked by high rates of violence, especially involving young residents. The research was developed through semi-structured interviews, analysis of statistical data and news regarding situations of violence in the neighborhoods. In this sense, "embolamentos" are part of a network of youthful sociabilities - presenting complex relationships with bondes and facções - as well as with the urban space from which it originates.
Keywords: Embolamento; Sociabilidade; Juventude; Periferia; Violência; Embolamento; Sociability; Youth; Suburb; Violence; ACCNPQ::Ciências Humanas::Sociologia